Evaluating the effectiveness of Nepal’s Disaster Management Policies in protecting life and Property (Sambahak: Human Rights Journal, 2024)
This article critically evaluates the effectiveness of Nepal’s disaster management policies in safeguarding life and property, with a focus on the alignment of these policies with international human rights standards. Using a qualitative doctrinal approach, the study analyzes legal documents, government reports, and case studies of recent disasters, particularly the 2015 Gorkha earthquake. It highlights the evolution of Nepal’s disaster management framework, notably the Disaster Risk Reduction and Management Act 2017, which shifted the country from a reactive to a proactive approach. Key areas assessed include early warning systems, emergency response coordination, and post-disaster rehabilitation, alongside protection for vulnerable populations. The study identifies gaps in policy implementation and enforcement, particularly at local levels, and suggests improvements to enhance resilience. It emphasizes the importance of integrating human rights into disaster management and offers recommendations for strengthening Nepal’s disaster preparedness, response, and recovery mechanisms to better protect life, property, and rights amidst increasing disaster risks due to climate change.